A Review on Mitochondrial Genome of Ants (Hymenoptera: Formicidae) - Kolondam, Beivy Jonathan; Tallei, Trina Ekawati; Koneri, Roni; Abas, Abdul Hawil; Mamahit, Juliet Merry Eva (Heca Sentra Analitika, 2023)
Ants, which are members of the Formicidae family, have been the subject of considerable scientific scrutiny due to their remarkable diversity and ecological importance. Extensive research endeavors have been directed towards understanding the complex behaviors and ecological responsibilities exhibited by these organisms. The advent of cutting-edge sequencing technology in recent times has sparked a significant breakthrough in the deciphering of mitochondrial genomes in many animals, including ants. The objective of this review paper is to provide an informative summary of the mitochondrial DNA of ants. Exploring the intricate structural aspects, we investigate the genetic diversity that exists in the mitochondrial genomes of ants. The investigation of evolutionary processes provides insight into the complex alterations that have shaped genomes throughout time. The broader ramifications of these genetic differences for the fields of ant biology and conservation are thoroughly considered. An examination is conducted on the structural characteristics, genetic variations, and evolutionary features of ant mitochondrial genomes, along with an investigation into their physiological impacts. As the molecular complexities of ant mitochondrial genomes are revealed, there is an opportunity to further explore their realm, leading to a more comprehensive comprehension of these extraordinary organisms.